TANDA V PADA FOTOGRAFI POTRET DALAM KOLEKSI FOTO 2017: SHUTTERSTOCK - KASENDA, ALVALINO RICLEF (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research which is entitled â€œTanda V pada Fotografi Potret dalam Koleksi Foto 2017: Shutterstockâ€ is focused on connotation and myths that can be found in the portrait photography. The aims of this research are to analyze the connotation and and describe the myths of V-sign that can be found in portrait phorography. This research uses Roland Barthesâ€Ÿ theory in the process of analyzing the connotation and describing the myths of V-sign. The source of portrait photography was taken from photo collection 2017: Shutterstock, published by the Jon Oringer on their website at www.shutterstock.com. The method of this research is descriptive method. Every connotation and myth of V-sign found in the portrait photography was analyzed and described according to the process called order of signification.Â  The result of this research shows that based on the theory of Barthes there are seven different connotations contained in V-sign in the portrait photography. Those are happiness, underestimate, relief, success, independence, relax, political campaign. In addition, there are five kinds of myth contained in V-sign in the portrait photography. Those are are salute, humiliation, peace, victory, contradiction, freedom, two fingers salute.Â  The writer hopes that this study will help the reader to understand about semiotics especially connotation and myth and how those convey deeper understandings of meanings in portrait photography. Â Keywords: V-sign, connotation and myth, portrait photography